FASHION SEBAGAI MEDIA KOMUNIKASI (ANALISIS SEMIOTIK FASHION KONTROVERSIAL LADY GAGA) - CHRISTIANY JUDITHA (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2015)
American pop singer Lady Gaga is known for controversial with her fashions unusual. Many religious groups in several countries rejected it because of the controversy. The reason Lady Gaga often use symbols that are insulting and blasphemous religious costumes reflected her shows. This study aimed to get a picture of Lady Gaga's controversial fashion as a medium of communication. The method used is to approach Pierce semiotic analysis to determine the meaning of the symbols in fashion Lady Gaga controversy which consists of a sign, object and interpreter. The result of the study concludes that Lady Gaga is known for using the symbols of religious insult. However, despite much criticism, but through costumes that Lady Gaga wants to communicate about him being free and not governed by any rules and free to do whatever he likes, including wearing fashion.